2004
DOI: 10.1002/mrdd.20046
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of core deficits in autism

Abstract: The goal of this review of the research literature is to discuss approaches to the early detection of autism in infancy. Early detection would enable diagnoses to be made before 18 months of age rather than at 24-30 months, the age where diagnoses start to be made now. After summarizing the criteria for a deficit to be considered "core" to the disorder, the literature on research strategies used in early detection is examined. In order to guide the design of future studies, the review then turns to an overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 125 publications
(115 reference statements)
0
54
0
3
Order By: Relevance
“…This finding supports the criterion of uniqueness of a core deficit in autism (Williams et al 2004). To establish the specificity of imitation problems, research is carried out that contrasts different functions and abilities across groups, testing the hypothesis that imitation problems are deficient in the autism group while other problems are not involved, or that imitation problems are specific rather than being part of a more general problem (Sigman et al 2004). Results of Williams and colleagues' meta-analysis revealed that mental delay and motor skill impairment account for some impairment but by no means for all of it.…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…This finding supports the criterion of uniqueness of a core deficit in autism (Williams et al 2004). To establish the specificity of imitation problems, research is carried out that contrasts different functions and abilities across groups, testing the hypothesis that imitation problems are deficient in the autism group while other problems are not involved, or that imitation problems are specific rather than being part of a more general problem (Sigman et al 2004). Results of Williams and colleagues' meta-analysis revealed that mental delay and motor skill impairment account for some impairment but by no means for all of it.…”
mentioning
confidence: 58%
“…Do imitation problems reflect a core characteristic in autism? A symptom is considered to be a core characteristic of autism if it is unique to autism, specific and universal (Sigman et al 2004). In addition, a deficit must fulfil the criteria of persistency (Hobson and Lee 1999), precedence (Rogers 1999) and broadness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The social interaction and orientation problems of infants with autism may decrease the amount of attention to their mothers (Sigman et al 2004). Children with autism with a secure attachment relationship may however show more reciprocal interaction with their caregiver compared to their counterparts with a disorganized attachment relationship.…”
Section: Joint Attention Attachment and Autismmentioning
confidence: 99%
“…The three basic requirements are universality (that is, that the deficit is manifested in all or almost all individuals with autism), specificity (that is, that the disorder involves a domain-specific deficit in this particular area), and uniqueness (that is, that the deficit is not manifested by most individuals with other clinical diagnoses) (Sigman, 1994(Sigman, , 1996Wagner, Graniban, & Cichetti, 1990;Zelazo, Burack, Benedetto, & Frye, 1996;Zelazo, Burack, Boseovski, Jacques, & Frye, 2001). In order to address these issues, researchers must carefully examine the characteristics of the groups employed in their studies.…”
Section: The Search For a Core Deficitmentioning
confidence: 99%